การพัฒนาคุณธรรมจริยธรรมและสมรรถนะที่พึงประสงค์ของครูตามแนวพุทธศาสนาในภาคตะวันออกเฉียงเหนือ - สุวรรณศรี, สุรพันธ์; จำเริญสาร, วงศ์ชนก; โสภาจร, วัชรพงษ์; นทีศิริกุล, สุริยา; อามาตย์มุลตรี, เอี่ยม (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด; Vol 4 No 1 (2567): มกราคม – เมษายน 2567, 2024)
บทความวิจัยนี้มีวัตถุประสงค์ 1) เพื่อศึกษาสภาพการจัดกิจกรรมการพัฒนาคุณธรรมจริยธรรมและสมรรถนะที่พึงประสงค์ของครูตามแนวพุทธศาสนา 2) เพื่อสร้างและพัฒนารูปแบบปฏิบัติกิจกรรมการพัฒนาคุณธรรมจริยธรรมและสมรรถนะที่พึงประสงค์ของครูด้วยการประยุกต์ใช้หลักธรรมอริยสัจสี่ และ 3) เพื่อประเมินรูปแบบปฏิบัติกิจกรรมคุณธรรมจริยธรรมและสมรรถนะที่พึงประสงค์ของครู ด้วยการประยุกต์ใช้หลักธรรมอริยสัจสี่  ได้ดำเนินการตามขั้นตอนการวิจัยและพัฒนา เป็นการวิจัยเชิงทดลอง กลุ่มตัวอย่างที่ใช้ในการวิจัยเป็นครูในโรงเรียน จำนวน 329 คน ใช้สถานศึกษาเป็นหน่วยสุ่มได้มาโดยการสุ่มแบบแบ่งชั้นภูมิ ผู้ทรงคุณวุฒิในการประชุมกลุ่มสนทนา จำนวน 15 รูป/คน กลุ่มตัวอย่างในการทดลองรูปแบบการปฏิบัติกิจกรรมเป็นครูจาก 6 โรงเรียน โรงเรียนละ 3 คน รวม 18 คน ได้มาโดยการสมัครใจเข้ารับการอบรม เครื่องมือที่ใช้ในการวิจัยเป็นแบบสอบถาม จำนวน 50 ข้อ เป็นชนิดมาตราส่วนประมาณค่า 5 ระดับ โดยใช้สถิติพื้นฐาน ค่าเฉลี่ยค่าร้อยละ ค่าส่วนเบี่ยงเบนมาตรฐาน และสถิติทดสอบสมมุติฐาน t–test (Dependent Sample)            ผลการวิจัยพบว่า 1) สภาพการจัดกิจกรรมการพัฒนาคุณธรรมจริยธรรมและสมรรถนะที่พึงประสงค์ของครูตามแนวพุทธศาสนา โดยรวมอยู่ในระดับปานกลาง 2) ผลการดำเนินการทดลองรูปแบบปฏิบัติกิจกรรมการพัฒนาคุณธรรมจริยธรรมและสมรรถนะที่พึงประสงค์ของครู โดยการประยุกต์ใช้หลักธรรมอริยสัจสี่กับกลุ่มตัวอย่างที่เป็นครูผู้สอนเมื่อเปรียบเทียบคะแนนเฉลี่ยผลการทดสอบก่อนการอบรมและหลังการอบรม อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 ซึ่งเป็นไปตามสมมุติฐานและรูปแบบปฏิบัติกิจกรรมพัฒนาคุณธรรมจริยธรรมและสมรรถนะที่พึงประสงค์ของครูที่สร้างขึ้นมีประสิทธิภาพตามเกณฑ์ เท่ากับ 85.83/85.56 สูงกว่าเกณฑ์มาตรฐานที่ตั้งไว้ คือ 80/80 มีค่าดัชนีประสิทธิผลเท่ากับ 0.602 แสดงให้เห็นว่ารูปแบบกิจกรรมพัฒนาคุณธรรมจริยธรรมและสมรรถนะที่พึงประสงค์ของครู ส่งผลให้ผู้เข้าอบรมมีความรู้เพิ่มขึ้น 0.602 หรือเพิ่มขึ้นคิดเป็นร้อยละ 60.20 ของคะแนนสูงสุดที่สามารถจะเพิ่มได้ ผู้เข้าอบรมมีความพึงพอใจต่อการจัดอบรม โดยใช้รูปแบบกิจกรรมพัฒนาคุณธรรมจริยธรรมและสมรรถนะที่พึงประสงค์ของครู โดยรวมอยู่ในระดับพึงพอใจมากที่สุด 3. การประเมินรูปแบบปฏิบัติกิจกรรมพัฒนาคุณธรรมจริยธรรมและสมรรถนะที่พึงประสงค์ของครู ตามแนวพุทธศาสนา พบว่า โดยรวมมีค่าเฉลี่ยความเหมาะสมอยู่ในระดับมากที่สุด เมื่อจำแนกเป็นรายด้าน พบว่า โดยรวมมีค่าเฉลี่ยอยู่ในระดับมากที่สุด รองลงมาได้แก่ด้านความถูกต้อง และด้านความเหมาะสม ส่วนด้านความเป็นไปได้มีค่าคะแนนเฉลี่ย เป็นลำดับสุดท้าย              The objectives of this research article are 1) to study the conditions for organizing activities to develop morality, ethics and desired competencies of teachers according to Buddhist principles. 2) To create and develop a practice model for activities to develop morality, ethics and desired competency of teachers by applying the principles of the Four Noble Truths and 3. to evaluate the practice model, morality, ethics, and desired competencies of teachers. By applying the principles of the Four Noble Truths Has carried out the research and development process as experimental research. Sample group used in research There were 329 school teachers. Educational institutions were used as the random units obtained by stratified random sampling. Experts in focus group meetings totaling 15 people/person. The sample group in the experiment of the practice model of teaching activities from 6 schools, 3 people per school, totaling 18 people, was obtained by volunteering. Receive training The research instrument was a 50-item questionnaire, a 5-level rating scale, using basic statistics. Average percentage value Standard deviation and hypothesis testing statistics t-test (Dependent Sample).            The research results found that: 1) Conditions for organizing activities to develop morality, ethics and desired competencies of teachers according to Buddhist principles. Overall, it is at a moderate level. 2) The results of the experiment of the activity model for developing teachers' morality, ethics and desired competency. By applying the principles of the Four Noble Truths to a sample group of teachers when comparing the average scores of the test results before the training and after. Training Statistically significant at the .05 level, which is in line with the assumptions and practice model of activities to develop morality, ethics, and desired competencies of teachers. That was created was effective according to the criteria equal to 85.83/85.56, higher than the standard criteria set, which is 80/80, with an effectiveness index value of 0.602, indicating that the activity format develops morality, ethics and desired competency of teachers. As a result, the participants' knowledge increased by 0.602, or an increase equivalent to 60.20 percent of the maximum score that could be increased. 3) Evaluation of activities to develop teachers' morality, ethics, and desired competencies. According to Buddhism, it was found that overall, the mean level of appropriateness was at the highest level. When classified into each aspect, it was found that overall, the mean level was at the highest level. Followed by accuracy and appropriateness. As for the feasibility aspect, the average score was is the last order.